Peningkatan Kualitas Karya Ilmiah Melalui Pelatihan Dan Pendampingan Mendeley Bagi Mahasiswa Olahraga Papua - Prasetyo, Muhammad Teguh; Putra, Miftah Fariz Prima; Hidayat, Rodhi Rusdianto; Khasanah, Fachrun Nisa Sofiyah; Kafiar, Sifra (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
This community service activity was motivated by the low literacy of students in utilizing reference management applications in the preparation of scientific papers. The objective of the activity was to improve students' understanding and skills in using Mendeley effectively and independently. The implementation method included training, development of a guide module, integration of use in lecture assignments, as well as mentoring and evaluation. The results of the activity showed significant improvements, where 100% of participants were able to use Mendeley for citations and automatic bibliography compilation independently. In addition, there was an increase in the timeliness of assignment submissions and the quality of students' scientific writing. This comprehensive and sustainable approach has proven effective in forming more systematic and technology-based academic habits. This activity has the potential to be implemented more widely to support improving the quality of scientific writing in higher education.